Densidade mineral óssea em idosos e presença de fatores de risco nutricionais para osteoporose - Dourado, Caroline Marangon (2012)
Objectives: Relate to bone mineral density (BMD) in elderly patients with the presence of nutritional risk factors for osteoporosis. Methods: In the elderly of both sexes, aged over 60 years, the BMD was assessed by examining Dual Energy X-Rain absorptiometry (DXA). Economic and demographic data were collected on a structured questionnaire. The identification of nutritional risk factors was verified by a Food Frequency Questionnaire (FFQ) and Mini Nutritional Assessment (MNA®). The level of significance in this study was 5%. Results: The sample consisted of 71 elderly patients, 10 men (14.1%) and 61 women (85.9%). The mean age was 68.77 ± 6.73 years. In multiple linear regression model adjusted by gender (p=0.009), sodium intake (p=0.011) and vitamin B12 (p=0.003) were the variables that showed a higher correlation with bone mineral density. Risk of malnutrition and malnutrition (p=0.021), as well as family history of osteoporosis (p=0.020) are also factors that interfered negatively in bone mineral density. The variables smoking, physical inactivity, alcohol use, intake of protein, total dietary fiber, caffeine, vitamin C and potassium showed no significant impact on changes in bone mineral density in the sample in this study. Conclusions: High sodium intake and low intake of vitamin B12 were the major nutritional risk factors for osteoporosis that affect the bone mineral density in elderly. Family history, female gender and nutritional status (risk of malnutrition) also contributed to the reduction of bone mass